Effect of elective cerclage versus rescue cerclage in pregnancy and its pregnancy outcome - Gupta, Surbhi; Kumari, Gitanjali; Taralekar, Vaishali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Prolongation of the pregnancy in cases of incompetence of cervix or short cervix can be done by prompt diagnosis at the correct time with a decision on encirclage taken at the right time. An observational retrospective study conducted over a period of 6 months in a tertiary care centre enrolling 14 pregnant women who had various risk factors like multiple gestation, short cervix, cervical incompetence, bad obstetric history, anomalous uterus, in vitro fertilization technique, history of primary infertility ,recurrent abortions and mid-trimester losses or preterm delivery, and the results were interpreted with various tables and charts showing the benefits of elective versus emergency encirclage. Through the study, it was found that there wasn't any significant difference in the incidence of a patient who underwent cervical encirclage whether the patient had a prior antenatal registration or not. 71% of the patients enrolled for encirclage were primigravida and the most common gestation age was between 12-24 weeks. The most common age group was 21-30 years of age. Cervical incompetence and short cervix were the most important risk factor needed for cervical cerclage. Most of the patients delivered at around 34-37 weeks of gestation. 21.4% patient underwent rescue cerclage and delivered between 34-37 weeks of gestation. 57.14% underwent elective cerclage and delivered near term. Elective cerclage has a better outcome of pregnancy to reach near term than rescue cerclage.